Sustained therapeutic effect of an anti-inflammatory peptide encapsulated in nanoparticles on ocular vascular leakage in diabetic retinopathy - Qu, Qiang; Park, Kyoungmin; Zhou, Kevin; Wassel, Drew; Farjo, Rafal; Criswell, Tracy; Ma, Jian-xing; Zhang, Yuanyuan (Frontiers in Cell and Developmental Biology, 2022)
Pigment epithelium-derived factor (PEDF) is an endogenous Wnt signaling inhibitor in the serine proteinase inhibitors (SERPIN) super family. Reduced PEDF levels in the vitreous are associated with pathological changes including retinal vascular leakage and inflammation in diabetic retinopathy (DR). Intravitreal delivery of PEDF represents a promising therapeutic approach for DR. However, PEDF has a short half-life after intravitreal injection, which represents a major hurdle for long-term treatment. Here we report the prolonged therapeutic effects of a 34-mer peptide of the PEDF N-terminus, encapsulated in poly (lactic-co-glycolic acid) (PLGA) nanoparticles (PEDF34-NP), on DR. Administration of PEDF34-NP prevented hypoxia-induced expression of VEGF and intercellular adhesion molecule 1 (ICAM-1) levels in cultured retinal cells. PEDF34-NP significantly ameliorated ischemia-induced retinal neovascularization in the oxygen-induced retinopathy model, and significantly reduced retinal vascular leakage and inflammation in streptozotocin-induced diabetic rats up to 4 weeks after intravitreal injection, as compared to PLGA-NP control. Intravitreal injection of PEDF34-NP did not display any detectable toxicities to retinal structure and function. Our findings suggest that PEDF34-NP can confer sustained therapeutic effects on retinal inflammation and vascular leakage, and has potential to become a novel treatment of DR.